2019
DOI: 10.1186/s12881-019-0832-9
|View full text |Cite
|
Sign up to set email alerts
|

A novel risk score system for assessment of ovarian cancer based on co-expression network analysis and expression level of five lncRNAs

Abstract: Background: Ovarian cancer (OC) is the most deadly gynaecological cancer, contributing significantly to female cancer-related deaths worldwide. Improving the outlook for OC patients depends on the identification of more reliable prognostic biomarkers for early diagnosis and survival prediction. The various roles of long non-coding RNAs (lncRNAs) in OC have attracted increasing attention. This study aimed to identify a lncRNA-based signature for survival prediction in OC patients. Methods: RNA expression data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 62 publications
0
25
0
Order By: Relevance
“…Ovarian cancer is a grave gynecological tumor and there are not many studies concerning the role of GAS5 in it or its association with chemoresistance in this tumor. However, similar to other gynecological tumors, it seems that all studies converge to the conclusion that GAS5 acts as a tumor suppressor in ovarian cancer, as well [44][45][46][47]. In a recent study, GAS5 was found to be down-regulated in this disease [41].…”
Section: Gas5 In Ovarian Cancermentioning
confidence: 70%
“…Ovarian cancer is a grave gynecological tumor and there are not many studies concerning the role of GAS5 in it or its association with chemoresistance in this tumor. However, similar to other gynecological tumors, it seems that all studies converge to the conclusion that GAS5 acts as a tumor suppressor in ovarian cancer, as well [44][45][46][47]. In a recent study, GAS5 was found to be down-regulated in this disease [41].…”
Section: Gas5 In Ovarian Cancermentioning
confidence: 70%
“…Exploring the abnormal expression, function and mechanism of lncRNA in the development of OC can provide biomarkers and therapy targets [22]. For example, a recent study reports that a predictive model, based on the expressions of lncRNAs, GAS5, HCP5, PART1, SNHG11 and SNHG5 included, can identify OC patients at high risk of poor prognosis [23]; the up-regulation of LINC00319 expression accelerates the proliferation, migration and invasion of OC cells [24]; LncRNA PTAR expression is up-regulated in OC and it promotes the EMT and metastasis of OC cells [25]. In this work, we focused on the role of LINC01094 in the progression of OC and found that LINC01094 was highly expressed in OC tissues and cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, bioinformatics analysis of expression profile has been widely and rapidly used to identify novel and more effective potential biomarkers for cancer treatment and patient prognosis (3)(4)(5)(6)(7). However, how to transform the microarray information into a better understanding of biology through traditional differential expression analysis is still a major challenge.…”
Section: Introductionmentioning
confidence: 99%